Transplantation of PEGylated islets enhances therapeutic efficacy in a diabetic nonhuman primate model. Issue 3 (13th November 2019) - Stabler, Cherie L.; Giraldo, Jaime A.; Berman, Dora M.; Gattás‐Asfura, Kerim M.; Willman, Melissa A.; Rabassa, Alexander; Geary, James; Diaz, Waldo; Kenyon, Norman M.; Kenyon, Norma S.
Abstract : Islet cell transplantation can lead to insulin independence, reduced hypoglycemia, and amelioration of diabetes complications in patients with type 1 diabetes. The systemic delivery of anti‐inflammatory agents, while considered crucial to limit the early loss of islets associated with intrahepatic infusion, increases the burden of immunosuppression. In an effort to decrease the pharmaceutical load to the patient, we modified the pancreatic islet surface with long‐chain poly(ethylene glycol) (PEG) to mitigate detrimental host‐implant interactions. The effect of PEGylation on islet engraftment and long‐term survival was examined in a robust nonhuman primate model via three paired transplants of dosages 4300, 8300, and 10 000 islet equivalents per kg body weight. A reduced immunosuppressive regimen of anti‐thymocyte globulin induction plus tacrolimus in the first posttransplant month followed by maintenance with sirolimus monotherapy was employed. To limit transplant variability, two of the three pairs were closely MHC‐matched recipients and received MHC‐disparate PEGylated or untreated islets isolated from the same donors. Recipients of PEGylated islets exhibited significantly improved early c‐peptide levels, reduced exogenous insulin requirements, and superior glycemic control, as compared to recipients of untreated islets. These results indicate that this simple islet modification procedure may improve islet engraftment and survival in the setting of reduced immunosuppression. Abstract : Grafting PEG polymer chains onto nonhuman primate islets improves early c‐peptide levels, reduces exogenous insulin requirements, and gives superior glycemic control in diabetic nonhuman primate recipients when compared to unmodified islets.